(untitled) (Socio-economic relations in the digital society, 2019)
Сhanges in economic conditions give rise to new problems of insuffi cient Gcapitalization of the banking system of Ukraine. Th e problem of capitalization of banks has become important in the early development of the domestic banking system. There trospective analysis of process of capitalization of the banking system of Ukraine is conducted.Тhe dynamics of own capital of the banking system of Ukraine and the largest banks; capital adequacy ratio, norms of capital are discussed. Certainly problems, directions and prospects of improvement of management of capitalization processes, at thelevel of the banking system.